The Effect of different level of Pomegranate molasses on performance, egg quality trait, serological and hematological parameters in older laying hens: The Use of pomegranate molasses as growth promoter in poultry nutrition - Iqbal, Aamir; Bayram, Ismail; Gultepe , Eyup Eren; Uyarlar, Cangir; Õzçınar, Ümit; Cetingul, İbrahim Sadi (Progress in Nutrition, 2021)
The current study was planned to investigate the effects of pomegranate molasses (PM) on performance, egg quality and blood parameters in laying hens. A total of 240 Babcock white laying hens (58 weeks old) were divided into 5 groups (n=48) with 8 subgroups having 6 hens in each. Pomegranate molasses was added in the drinking water to experimental groups with 0 %, 0.1%, 0.25 %, 0.5%, and 1%, respectively during 4 weeks. Results showed that egg weight values were same in all groups exclude 1% pomegranate molasses group over control however no significant (P>0.05) result were observed on feed consumption, egg production, FCR, egg mass, egg yolk cholesterol, live body weights, and water consumption. Similarly during mid-study analyses, egg quality parameters were remained not significant (P>0.05) by the supplementation of pomegranate molasses while during final analyses, egg yolk color had positively (P